EDUCATIONAL IMPORTANCE OF TEACHING GEOGRAPHY IN SECONDARY SCHOOLS - B.R.Umaraliyeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The study of geography enriches the personal experience of secondary school students, allows them to gain knowledge about the laws of cause and effect, phenomena and processes that occur in the environment and nature around us.